2021
DOI: 10.1016/j.toxrep.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization & evaluation of venom neutralization potential of silver nanoparticles mediated Alstonia scholaris Linn bark extract

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There have been a few reports on the formulation of nanoparticles to reduce the toxic effects of snake venom proteins. Silver nanoparticles prepared in the presence of Alstonia scholaris Linn bark extract effectively neutralized Viper russelli venom ( Ghosh et al, 2021 ). Another report states that 2-hydroxy-4-methoxybenzoic acid (HMBA) from the root extract of the Indian Sarsaparilla ( Hemidesmus indicus ) has viper venom neutralizing effects in animal models ( Gomes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few reports on the formulation of nanoparticles to reduce the toxic effects of snake venom proteins. Silver nanoparticles prepared in the presence of Alstonia scholaris Linn bark extract effectively neutralized Viper russelli venom ( Ghosh et al, 2021 ). Another report states that 2-hydroxy-4-methoxybenzoic acid (HMBA) from the root extract of the Indian Sarsaparilla ( Hemidesmus indicus ) has viper venom neutralizing effects in animal models ( Gomes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the rapid development in the uses of nanoparticles in the medical and industrial fields, many researchers have focused on devising new methods to reduce the toxicity of these materials [ [41] , [42] , [43] , [44] ]. In this study, we have examined the sexual behavior, body and weight of reproductive organs, spermatotoxicity, serum testosterone level, apoptosis in germ cells, testicular histopathology and antioxidant biomarkers in the testis of mice exposed to Ag-NPs and the protective effects of YO-NPs against Ag-NPs toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It may be better to pre-treat the animals with YO-NPs instead of the treatment after Ag-NPs exposure [ 33 ]. However, the NPs effects differ depending on the synthesis method (chemical or biological synthesis) and coating agent used [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment with a low and high dose of MO-AgNPs significantly improved the haematological indices dosedependently and ameliorated the pathological defects noticed in the heart of envenomed treated rats. The observed improvement could be attributed to the neutralizing potentials of MO-AgNPs after treatment as studies have reported the neutralizing potency of silver nano particles-based plant extract against venoms of snake species (Singh et al 2020;Ghosh et al 2021).…”
Section: He ×400mentioning
confidence: 97%